SUSTAINABILITY STRATEGY: APPLYING STRATEGIC MANAGEMENT IN BUSINESS FOR LONG-TERM GROWTH - Nenden Haprilwanti; Hamdan Yuapi, Sepa Munawar (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In the last decade, awareness of sustainability issues has increased significantly among businesses. Companies are now not only faced with the demands of achieving short-term profitability but also with the need to contribute positively to the environment and society, which in turn can ensure the continuity of operations and long-term business growth. This study aims to identify and analyze sustainability strategies implemented by companies to achieve long-term growth. This study utilizes the literature research method. The findings of this study found that the key success factors in implementing sustainability strategies include strong commitment from top management, integration of sustainability strategies with core business strategies, continuous innovation, and active collaboration with stakeholders. These companies face significant challenges in the form of internal resistance, regulatory uncertainty, and challenges in accurately measuring sustainability impacts. However, by adopting an adaptive approach and focusing on effective communication, education, and stakeholder engagement, they managed to overcome these challenges. The implementation of sustainability strategies has proven to not only help reduce the negative impact of business operations on the environment and society, but also open up new opportunities, enhance corporate reputation, and ultimately, ensure long-term growth.